Coordenação do cuidado às pessoas vivendo com HIV/aids: desafios no contexto da assistência ambulatorial especializada - Leadebal, Oriana Deyze Correia Paiva (2015)
Introduction: The different circumstances and health care complexities created by the HIV virus require specific approaches on the processes of production and management of care, carefully considering both the traits and demands of patients and families affected by the infection and the establishment of an integrated network of health services that provide a continuous and coordinated care. Objectives: To analyze specialized ambulatory coordination of the of HIV patient care through the lens of action offer and integration of health services. Method: Epidemiological research, transversal and interviews, involving 150 adults carrying the AIDS virus, users of the reference specialized ambulatory of the state of Paraíba, Brazil. The data was collected between July 2011 e July 2012, through interviews and chart lookup, using a structured questionnaire. It was then submitted to a statistical inference analysis through Statsoft’s Statistica 9.0 software, applying frequency measurement calculations, analysis of simple and multiple correspondence, analysis of robust variance and t-tests, calculations of average, standard deviation and trust intervals to 95% of satisfaction percentages related to the variables of offer and integration, logistical regression model, both simple and multiple linear regression models for influence analysis between risk, offer and integration. Results: The sociodemographic and clinic profiles are similar to the national scene, with a great expression of the “pardo” ethnicity on the studied population and good clinical indicator during the survey. We observed that 45.3% of the participants were included on the high risk category; there was a significant association of the composing variables to determine the risk score; the high influence of T CD4+ lymphocytes and undetectable viral charge for the assignment of the ‘no risk’ category; the presence of opportunistic diseases and clinical manifestations for the stratification of the risk group, and significant differences of medium risk according to the subjects’ job situation, economic class and skin color. The offer and integration were evaluated as regular, its main weaknesses the attention to psychosocial needs, the intersectional approach and information management. These factors and the high value indicators indicate a purely biological approach to health care. Among the subjects that presented unsatisfactory values to these components, most were in the high risk category. Conclusion: The weaknesses identified in offer and integration endanger the ambulatory’s performance inside the network for coordinated care. They also demand confrontational measures on both the micro and macro organizational levels for qualification of care directed to the needs of patients living with HIV/AIDS.